Calcium-Calmodulin-Involved Heat Shock Response of Neoporphyra haitanensis - Zheng, Hongyan; Xu, Yan; Ji, Dehua; Xu, Kai; Chen, Changsheng; Wang, Wenlei; Xie, Chaotian (Frontiers in Marine Science, 2022)
Increasing global temperatures have seriously affected the sustainable development of Neoporphyra haitanensis cultivation. Although several pathways are reported to be involved in the response of N. haitanensis to heat stress, it is unknown which ones are activated by signal transduction. Previously, we detected a large influx of calcium ions (Ca2+) in N. haitanensis under heat stress. In this study, we further investigated the specificity of Ca2+ signaling and how is it transduced. Transmission electron microscopy and Fv/Fm analyses showed that the Ca2+ signal derived from extracellular Ca2+ formed at the early stage of the response to heat stress, and the signal was recognized and decoded by N. haitanensis calmodulin (NhCaM). In yeast two-hybrid assays, DnaJ, a voltage-dependent anion channel, and a bromodomain-containing protein interacted with PhCaM1 in vivo. The transcript levels of the genes encoding these proteins increased significantly in response to heat stress, but decreased upon inhibition of NhCaM1, indicating that these interacting factors were positively related to NhCaM1. Additionally, a comparative transcriptome analysis indicated that Ca2+ signal transduction is involved in phosphatidylinositol, photosystem processes, and energy metabolism in N. haitanensis under heat stress. Our results suggest that Ca2+-CaM plays important roles in signal transduction in response to heat stress in N. haitanensis.